QLTI-01. THE EFFECT OF COMPLETE RESECTION OF CONTRAST-ENHANCING TUMOR ON SURVIVAL IN PATIENTS WITH GLIOBLASTOMA OVER A 16-YEAR PERIOD IN A GEOGRAPHICALLY DEFINED POPULATION. (14th November 2022) - Mendoza Mireles, Eduardo Erasmo; Vik-Mo, Einar Osland; Skaga, Erlend; Helseth, Eirik; Rønning, Pål Andre; Server, Andres; Brandal, Petter
Abstract: INTRODUCTION: The median survival for patients with glioblastoma is less than one year, and survival beyond five years is rare. Radiotherapy combined with chemotherapy has improved survival since its introduction in 2005. No new treatment modalities have been widely adopted after this, but treatment development has focused on achieving maximal resection and the introduction of coordinated clinical care pathways. We hypothesize that these changes in approach have resulted in an improved survival in surgically treated patients. METHODS: Retrospective analysis of a prospectively collected database in the adult population (2.4 million habitants) of South-Eastern Norway. Patients were divided in three periods; radiotherapy- (2003-2005), temozolomide- (2006-2012), and resection focused-period (2013-2019). Patients were also stratified according to age and grade of resection. Relative survival, Cox hazard-ratio, 3- and 5- year survival were calculated. RESULTS: We identified 1663 surgically treated glioblastoma patients eligible for the study. The median overall survival was 11.4 months. Complete resection of contrast-enhanced tumor (CRCET) was achieved in 387 (23.2%) patients. The frequency of CRCET increased during the observation time (32 - 116 - 239), but there was no increase in reoperation rates (13%). Significant improvement between the last period and the first two periods was observed (12.3 vs. 10.5 months, p < 0.006), with a significant increase in 3- and 5- year survival probability between the first two groups (p = 0.01). No difference was found in median survival in CRCET among periods. Patients with CRCET demonstrated significantly longer median survival than patients with non-CRCET (16.1 vs. 10.8 months; p < 0.001). Incidence in the elder group increased from 2.6 to 13.2 per 100, 000 habitants, and median survival doubled when CRT was achieved. CONCLUSIONS: There is an increase in median survival, 3- and 5- year survival probability when comparing time-periods. We suggest this survival benefit is related to improved CRCET rates.